Synthesis and structural characterization of zirconium complexes supported by tridentate pyrrolide-imino ligands with pendant N-, O- and S-donor groups and their application in ethylene polymerization. (4th January 2018) - Pinheiro, A. C.; da Silva, S. M.; Roisnel, T.; Kirillov, E.; Carpentier, J.-F.; Casagrande, Osvaldo L.
Abstract : Zirconium complexes supported by pyrrolide-imino ligands been synthesized and their catalytic behavior in ethylene polymerization has been investigated. Abstract : Zirconium complexes LZrCl x (THF) n [L = 2-(C4 H3 N-2′-CHN)C2 H4 NHPh, x = 3, n = 1, 2a ; L = 2-(C4 H3 N-2′-CHN)C6 H4 -2-OPh, x = 3, n = 0, 2b ; L = 2-(C4 H3 N-2′-CHN)C6 H4 -2-SPh, x = 3, n = 1, 2c ; L = 2-(C4 H3 N-2′-CHN)CH2 C6 H4 -2-OMe, x = 3, n = 0, 2d ; L = 2-(C4 H3 N-2′-CHN)C2 H4 NPh, x = 2, n = 0, 4a ] were prepared and characterized by elemental analysis, NMR spectroscopy, and by X-ray crystallography for2a and4a . In the solid state, 2a and4a are monomeric with the pyrrolide-imino-amine adopting a mer -configuration. Upon activation with methylaluminoxane (MAO), all Zr(iv ) precatalysts were active in ethylene polymerization and exhibited high thermal stability operating effectively at 100 °C with activities up to 453 kg(PE) mol[Zr] −1 h −1 . The high-density polyethylenes produced are strictly linear with melting temperatures in the range of 134–136 °C, and crystallinities varying from 56% to 70%.